Stock Valuation: The Role of Financial Ratio In Cement Companies On The IDX 2012-2022 - Hasanudin, Hasanudin (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This research aims to explore the role of Current Ratio, Debt to Equity Ratio, Return on Equity, and Dividend Payout Ratio on Price to Book Value in cement companies listed on the Indonesia Stock Exchange during the 2012-2022 period. This research aims to provide a better understanding of the factors that influence share valuation in the cement industry in Indonesia. The data analysis method used is panel regression with a significance level of 0.05, and STATA software is used to analyze the data. The research results show that Debt to Equity Ratio (DER) and Dividend Payout Ratio (DPR) have a significant influence on Price to Book Value (PBV) in cement companies listed on the Indonesia Stock Exchange. DER describes the relationship between equity and debt in a company's financial structure, while DPR reflects the percentage of net profit paid as dividends to shareholders. An increase in DER or DPR can positively or negatively affect the valuation of cement company shares. Return on Equity (ROE) and Current Ratio (CR) were not found to have a significant influence on PBV. ROE measures the efficiency of using equity in generating profits, while CR shows the company's ability to meet short-term obligations with current assets. These findings provide a deeper understanding for investors, financial analysts and other stakeholders in measuring company value and understanding the factors that contribute to stock valuation in the capital market.